Suicide mortality risk and protective factors - Beatriz Corona Miranda; Mariela Hernández Sánchez; Rosa Marina García Pérez (Universidad de Ciencias Médicas de La Habana, 2015)
Introduction: suicide is a universal problem with many causes. Gender, culture, ethnicity, family history, emotional disorders, violence, child abuse and unfavorable socioeconomic conditions are determining to consider in its epidemiology, existing risk and protective factors related to this behavior.  Objective: update aspects of suicide mortality and identify risk and protective factors involved in this intentionally self-inflicted injury. Material and Methods: a literature review was conducted in different databases of the Virtual Health Library, using the bases of SciELO, Ebsco, Cuban medical journals and other data were obtained 89 publications and 29 articles were included according to their importance, relevance and timeliness in the last five years. Results: the World Health Organization in its report in 2014 reported that the regions of low and middle income accounted for 75.5% of suicide mortality in the world, accounting for 50% of all violent deaths recorded between men and 71% among women. In Cuba is the ninth leading cause of death and the third in the group 10-19 years, increasing rates from 60 years of age. There are risks and protective factors at the individual, family, community, and institutional that are directly related to this conduct. Conclusions: early identification of risk factors and strengthening protective factors has a positive impact on suicide prevention strategies. Key words: intentionally self-inflicted injuries, suicidal behavior, risk and protective factors for suicide.